The nationalisation of historical monuments - Minea, Cosmin Tudor (2023)
A review of Dragan Damjanović and Aleksander Łupienko (eds.), Forging Architectural Tradition: National Narratives, Monument Preservation, and Architectural Work in the Nineteenth Century, New York, Oxford: Berghahn Books, 2022, 366 pages. ISBN 978-1-80073-337-4.